CT Virtual Intravascular Endoscopy in the Visualization of Coronary Plaques: A Pictorial Essay - Sun, Zhonghua; Xu, L. (Bentham Science Publishers, 2017)
Coronary CT angiography has been increasingly used to diagnose coronary artery disease with high diagnostic value achieved. For further assessment of coronary lumen stenosis, coronary CT angiography allows characterization of coronary plaques in terms of plaque morphology and composition. Coronary plaques are commonly assessed on 2D axial and multiplanar reformatted images. However, these visualization tools are limited to viewing extraluminal changes in the coronary artery but fail to provide intraluminal appearances of the coronary wall due to presence of plaques. In this pictorial essay, we present various intraluminal appearances of coronary wall and plaques with use of 3D virtual intravascular endoscopy (VIE) visualization in relation to different types of plaques. VIE appearances of coronary stents in patients treated with coronary stenting are also briefly demonstrated to show both normal stents and in-stent restenosis.